Carbon aerogels derived from waste paper for pipette-tip solid-phase extraction of triazole fungicides in tomato, apple and pear. (30th November 2022) - Sun, Haili; Feng, Juanjuan; Feng, Jiaqing; Sun, Mingxia; Feng, Yang; Sun, Min
Highlights: A facile method was developed for preparing carbon aerogels from waste paper. The carbon aerogel captured triazole fungicides in vegetables and fruits by PT-SPE. The carbon aerogel exhibited better extraction performance than some materials. A sensitive PT-SPE-GC-FID method was established to detect trace triazole fungicides. Abstract: In order to develop environmentally friendly, economical and facile preparation method of carbon aerogels (CAs), the waste printing paper as the raw material was combined with graphene oxide and carboxylic multi-walled carbon nanotubes to produce CAs (ρ = 44 mg cm −3 ). The CAs with different composition were investigated, the addition of graphene oxide led to the reduction of adsorption sites and the reduction of extraction performance. But the carbon nanotubes made CAs have a better pore structure. The CAs as adsorbent were loaded into a pipette-tip for solid-phase extraction of hexaconazole and diniconazole. Coupled with gas chromatography, an analytical method was established under the optimized conditions. The limits of detection were between 0.08 and 0.32 mg kg −1, the linear ranges were 0.96–200.0 mg kg −1 and 0.24–200.0 mg kg −1 . The relative recoveries were in the range of 81.0–119%. The results indicated that the method had potential application for the determination of triazole fungicides.